The Effect of Emotional Intelligence, Spiritual Intelligence and Intellectual Intelligence on Performance Employees at the Pamong Praja Police Unit Labuhan Batu District - Zulpadli Zulpadli; Ade Parlaungan Nasution; Muhammad Ali Al Ihsan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect ofemotional intelligence, spiritual intelligence and intellectual intelligence on the performance of employees in the Civil Service Police Unit of Labuhan Batu Regency. The population in this study were 233 people. The sampling technique used the Slovin formula with an error rate of 5%, so the sample size in this study amounted to 147 people. Methods of data collection using a questionnaire. The results of multiple linear regression analysis obtained the equation Y=1.086+0.210X1+0.145X2 +0.303X3. In the partial test (t test) the regression coefficient of the Emotional Intelligence variable (X1) obtained a t count value of 5.555 > t table 1.976 which means that the Emotional Intelligence variable has a positive and significant effect on the Employee Performance variable with a significant value of 0.000 < 0.05. The regression coefficient for the Spiritual Intelligence variable (X2) obtained a t-count value of 3.569 > t table 1.976, which means that the Spiritual Intelligence variable has a positive and significant effect on the Employee Performance variable with a significant value of 0.000 <0.05. The regression coefficient for the Intellectual Intelligence (X3) variable obtained a t-count value of 4.218 > t-table 1.976, which means that the Intellectual Intelligence variable has a positive and significant effect on the Employee Performance variable with a significant value of 0.000 <0.05. The results of the F test obtained the Fcount of 114.345 > Ftable 2.67 with a significant value of 0.000 <0.05 so it can be concluded that Emotional Intelligence, Spiritual Intelligence and Intellectual Intelligence simultaneously have a positive and significant effect on employee performance.that variable Emotional Intelligence, Spiritual Intelligence and Intellectual Intelligence have an influence of 70.6%on the Employee Performance variable, while the remaining 29.4% is influenced by other variables that are outside this research.